The Typology of Metalwork in the Safavid Miniatures (907-1135 AH) - Samira Seifali; Mehdi Keshavarz Afshar (نگره, 2021)
The metalwork in the Safavid era is remarkable in terms of visual aesthetics, ornamentation, and style. As in Safavid miniatures the objects are represented more than any other period, studying the miniatures can provide much information about the art of metalwork in this period. Also, the miniatures can be considered as one of the valuable resources in research on identifying the characteristics of Iranian cultural and social history in different eras. In miniatures, the goal has always been expressing a historical, epic, literary, and narrative through in the image, furthermore, the artist has attempted to convey the message of the text. But, in some periods this approach has changed to represent the real objects, and in some cases, the artists have tended to realism for drawing natural objects and they have paid attention to details. This particularly appeared in Safavid paintings in which the artist emphasizes the representation of the cloth, carpets, rugs, and buildings, etc. There are many collections of metalwork among the objects depicted in various parts of Safavid paintings. Today, several of these metal objects are in the museums and private collections, while some of them disappeared. The metal objects are one of the elements in the paintings that exist in different parts of the image. They can be seen inside or outside of the palaces. It can be said that the finest and the most beautiful type of Safavid metalwork in the paintings belong to the 10th century AH. The metal objects in the paintings have been used for different purposes. However, the presence of these valuable visual resources provides the basis for research on the social life, and by referring to them we can get much information about the range of metalwork of this period which is not available today. Therefore, the purposes of this study are identifying and classifying the metal objects in Safavid paintings and comparing them to the real ones in the museums. We also examine the use of these objects and how they are represented in the paintings. This study seeks to respond to the following questions: What is the relation between the images of the metal objects in Safavid paintings and the samples of real metalwork? And how the metal objects are represented? In this way, the problem of realism in painting is followed. For this, firstly, the miniatures were determined and those similar to the metal objects were eliminated. Then 23 samples were purposefully selected from the manuscripts from the 10th and the 11th centuries, including Shahnameh Tahmasebi (931 A.H.), Khamse Tahmasebi (931 A.H.), Khamsa (Quintet) by Nizami (946 A.H.), Divan by Amir Hasan Dehlavi (939 A.H.), Manuscripts from Qazvin – Mashhad school (second half of the 10th century) such as Haft Awrang (Seven Thrones) by Jami (964 A.H.), Shahnameh Shah Ismail II (984 A.H.),  also the manuscripts from  Habib al-Sayr (early 11th century), Bostan Sa’di (11th A.H.),  as well as single copies of the Isfahan School. The metal objects that are depicted in the paintings are: Tutya Surahi, Ewer, Candlestick, Lamp, Bath Pail (satl) and Drum. In the next step, the metal objects in the miniatures were identified and classified then they were compared with those that exist in museums. Finally, after analyzing the samples and comparing them with Safavid metalwork, it is concluded that the metal objects in these miniatures are depicted based on the metalwork of Safavid period and there is a realistic approach in Safavid paintings. Also, there are many similarities between the metal objects in miniatures and the real ones in terms of depicting separate parts of objects such as the base, the surface and the edge, flask and pitcher lids, and the ornamentations on the surface as well as the handle of the dishes. Moreover, despite the small size of the objects in the miniatures, the artist has not ignored the decoration of their surface. Besides, the existence of these different decorations on the objects in the paintings can be considered a sign of paying attention to representing metal objects according to reality. However, in some cases, such as candlesticks, according to the literature in this period, it seems that their pictures are similar to the pre-Safavid period, especially Timurid samples, in this way the same objects may have existed in Safavid palace to which the artist has paid attention. It can be said that despite the similarity in the general form of objects over time, we can see changes in form and different ornamentations on their surface in the paintings. Moreover, by referring to the findings of this research we can see many characteristics and functions of metalwork such as form, material, and ornamentation in the miniatures of this period. In this research, a descriptive-analytical method with a comparative approach was used and data were collected through library research by referring to museums' websites and online resources.